Importance of interculturality on foreign language teaching and cultural adaptation) - Estupiñán Lince, María Lorena (2023)
This paper on intercultural communication contains examples of traditions from diverse cultures and experiences of international students that illustrate how the world is understood and the importance of intercultural education. Nowadays, education must prepare young people for cultural dialogue, therefore the objectives of the study were to socialize the importance of intercultural education in foreign language teaching, to identify the differences and similarities in a culture that influence the process of adaptation in different countries, and to determine the signs and symptoms of culture shock experienced by international students in foreign countries. This sociolinguistic research used interviews and questionnaires with closed and open-ended questions. As it is a mostly qualitative investigation, the opinions, experiences, and advice of the participants recorded in written form allowed the grouping of the results into three general aspects to be considered by teachers who teach foreign languages: the image of the inner world (mental and emotional), stereotypes, and culture shock. In conclusion, it was found that the participants did not know the concepts of interculturality, the variations in the image of the inner world were significant from one culture to the other, stereotypes negatively affected intercultural communication, and the lack of knowledge of the culture influenced culture shock.